Socio-economic Situations and Determinants of ART Non-Adherence among Individuals Living with HIV/AIDS in Gondar Town Health Center, North west Ethiopia - Gebeyehu, Kelemu Fenta (Innovare Journal of Social Sciences, 2016)
Abstract Introduction: The epidemic of HIV / AIDS is affecting individual and community lives at different levels. To encounter such challenge HIV positive individuals are taking ART drugs but they often faced different challenge for taking the drug. Objective: The main objective of this study is to investigate the major socio-economic situations determinants of ART non- adherence among HIV/ AIDS positives in Gondar Town Health Center. Methods: To do so I have conducted a crossectional study with mixed method research that is both quantitative and qualitative methods. More specifically, I have employed questionnaires, FGD and in-depth interview to collect the actual data from respondents. Results: Based on the information gathered from respondents' majority of them are females (78%) whose age lies between 39-49 and socio-economically their major occupation is daily laborer and unemployed. As to the major challenges of taking ART drug personal, socio-economic situation that is being poor, lack of food, family level factors, shortage of professional counseling services and others are responsible. In conclusion, ART non- adherence is associated with the socio-economic condition of patients' personal, family and community level challenges. Key Words: Â HIV/ AIDS non- adherence, Antiretroviral Therapy, Socio- economic Challenges